Rehabilitation Nursing Practice Guiding for Patients with COVID-19 - Rehabilitation Nursing Committee of Chinese Society of Rehabilitation Medicine; Chinese Committee of Consortium of Cardiopulmonary Rehabilitation Nursing; Hui DING; Xiuyun LI; Cai'e ZHENG (康复学报)
The outbreak of Coronavirus Disease 2019 (COVID-19) has serious effect on physical and mental health of human. With the more understanding of COVID-19, we recognized that prevention and control measures, clinical practice and rehabilitation nursing are indispensable. Experts from Rehabilitation Nursing Committee of Chinese Society of Rehabilitation Medicine and Chinese Committee of Consortium of Cardiopulmonary Rehabilitation Nursing banded together to formulate the rehabilitation nursing practice guidings for patients infected with COVID-19. The contents of the guidings include four aspects: the rehabilitation nursing management, principles of rehabilitation nursing, training guiding of rehabilitation nursing, rehabilitation guiding of psychological and nutritional. The rehabilitation nursing management consists of the requirements of nosocomial infection management, regional safety management, patient management and companion, management of early warning system, which should strengthen the management of rehabilitation nursing, enforcing the standard for prevention and ward disinfection and quarantine, establishing the report system of early warning, reinforcing the management of inpatient and the companion. The principles of rehabilitation nursing emphasize the guidings of rehabilitation nursing on respiratory function, limb function, cardiac and pulmonary function. The training guidance of rehabilitation nursing mainly includes the training guidance of respiratory function, limb function, cardiac and pulmonary function. The rehabilitation guiding of psychological and nutritional mainly includes self-evaluation of psychological state, intervention of psychological problems and nutritional rehabilitation nursing, When nurses guide patients for the training of psychological and nutritional rehabilitation or respiratory, they will work according to the suitable measures to local conditions and different persons. These will help to improve patients'pulmonary ventilation function and lung function, restore their physical and psychological adjustment, enhance the activity ability. The measures are also in order to get the maximum improvement of patients'activities in daily living, quality of life and back into families and society quickly. The guiding aim is not only the management of rehabilitation nursing practice on patients withCOVID-19, but also the training of patients'respiratory function.